Does the low-density lipoprotein cholesterol play a key role in predicting metabolic syndrome in the Iranian adult population? - Hajian-Tilaki, Karimollah (Caspian J Intern Med, 2017)
BACKGROUND: The low density lipoprotein cholestrol (LDL-C) has an important role in the pathogenesis of cardiovascular disease but its association and predictive accuracy with metabolic syndrome (MetS) remains controversial. The objective of this study was to investigate the association and predictive ability of LDL-C with MetS. METHODS: We analyzed the data from a population-based cross-sectional study conducted on representative samples of an Iranian adult population. The demographic data, anthropometric measures and the lipid profiles were measured with standard methods, and MetS was diagnosed by ATP III criteria. Logistic regression model and ROC analysis were used to estimate the predictive accuracy of LDL-C and its association with MetS. RESULTS: The mean age (±SD) of participants with and without MetS was 47.6±12.5 years and 39.1±12.9 years, respectively (p=0.001). All anthropometric measures (body mass index, waist circumference, waist to hip ratio, waist to height ratio), systolic blood pressure, total cholesterol, triglycerides and fasting blood glucose were significantly higher in MetS, but a significantly higher difference in LDL-C was observed only in women. Accuracy of LDL-C in predicting MetS for men and women was 0.48 (95% CI: 0.43-0.54) and 0.55 (95% CI: 0.51-0.60), respectively. The unadjusted and adjusted odds ratios of different quartiles of LDL-C compared with 1(st) quartile did not reach to a significant level. CONCLUSION: Serum LDL-C level is not significantly associated with MetS but exhibits a weak ability in predicting MetS in women.